A novel signal amplification strategy for highly specific and nonenzymatic isothermal electrochemiluminescence detection of tumour markers. Issue 7 (3rd February 2020) - Liu, Yan; Guo, Xin; Fan, Zhijin; Liao, Yuhui; Yu, Ying; Guo, Manli; Cao, Yujuan; Zhu, Debin
Abstract : A signal amplification strategy for highly specific and nonenzymatic isothermal electrochemiluminescence detection of microRNA was developed. The limit of detection was as low as 4 fmol, which was superior to that for the reported linear DNA method. Abstract : The small size of microRNAs in biofluids presents challenges for detection by quantitative real-time polymerase chain reaction (qRT-PCR). In this work, a sensitive electrochemiluminescent probe based on dendritic DNA and streptavidin-coated magnetic beads was fabricated, and good amplification efficiency and sample loading efficiency were obtained. Thus a nonenzymatic and isothermal electrochemiluminescence method was proposed for the sensitive detection of miRNA-21. The limit of detection was as low as 4 fmol, which was superior to that for the reported linear DNA method. In real tumor cell analysis, the proposed method achieved equivalent detection results to the qRT-PCR method, guaranteeing the validity and feasibility of routine inspection.